Effect of high phosphate diet on the formation of dentin in Fam20c‐deficient mice. (27th April 2021) - Zhang, Hua; Xu, Qian; Lu, Yongbo; Qin, Chunlin
Abstract: FAM20C (family with sequence similarity 20‐member C), a kinase that phosphorylates secretory proteins, plays essential roles in various biological processes. In humans, mutations in FAM20C gene cause Raine syndrome, an autosomal recessive hereditary disease manifesting a broad spectrum of developmental defects including skeletal and craniofacial deformities. Our previous studies revealed that inactivation of Fam20c in mice led to hypophosphatemic rickets and that high phosphate (hPi) diet significantly improved the development of the skeleton in Fam20c ‐deficient mice. In this study, we evaluated the effects of hPi diet on the formation of dentin in Fam20c ‐deficient mice, using plain x‐ray radiography, micro–computed tomography (µCT), histology, and immunohistochemistry. Plain x‐ray radiography and µCT analyses showed that the hPi diet improved the dentin volume fraction and dentin mineral density of the Fam20c ‐deficient mice. Histology analyses further demonstrated that the hPi diet dramatically improved the integrity of the mandibular first molars and prevented pulp infection and dental abscesses in Fam20c ‐deficient mice. Our results support that the hPi diet significantly increased the formation and mineralization of dentin in Fam20c ‐deficient mice, implying that hypophosphatemia is a significant contributor to the dentin defects in Fam20c ‐deficient subjects.